Compostos sulfurados em asfaltos: influência do processo de envelhecimento na composição das frações maltênicas e asfaltênicas - Claussen, Luís Evandro (2013)
The behavior of sulfur compounds in asphalt cements can be studied in a more comprehensive way through the separation of maltenes and asphaltenes and their respective fractions. Thus, the ASTM D4124 method was applied for the separation of maltenes and asphaltenes in acidic, basic and neutral fractions of súlfur compounds. Herein, it could be observed that the sulfur heteroatom appears in higher levels as a less reactive fraction (neutral compounds) for virgin asphalts. The aging process lead to an increase of at least 20% for the polar fractions of sulfur, which is related to here to acidic and basic sulfur compounds. From this speciation results, a classification of the asphalt samples can be proposed taking into account the calculated reactivity in terms of polar (acidic/basic) and neutral compounds. These results permit to infer that a higher content of asphaltenes does not necessarily imply in a higher reactivity of the asphaltic binder. So the presence of specific functional groups related to these heteroatoms (e.g. sulfur) may be definitive for a greater or lesser susceptibility of the binder to the aging processes.